2017
DOI: 10.1161/jaha.117.006054
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Prognostic Impact of Prophylactic Oral Anticoagulation in Anterior ST‐Segment Elevation Myocardial Infarction Patients With Left Ventricular Dysfunction

Abstract: BackgroundThe contemporary role of prophylactic anticoagulation following extensive anterior wall ST‐segment myocardial infarction (STEMI) is unclear.Methods and ResultsWe evaluated anterior STEMI patients with left ventricle dysfunction (left ventricular ejection fraction ≤40%) (“high risk”), categorized by prophylactic warfarin use, within a regional STEMI. Patients with pre‐existing atrial fibrillation were excluded. The primary outcome was an adjusted (for Global Registry of Acute Coronary Events risk scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Shavadia et al recently reported similar results with no benefit for triple therapy in a series of consecutive STEMI patients with anterior LV dysfunction. 130 In patients with established LVT who undergo PCI for an ACS or non-ACS indication we make the following recommendation.…”
Section: Lvt Formation After MImentioning
confidence: 99%
“…Shavadia et al recently reported similar results with no benefit for triple therapy in a series of consecutive STEMI patients with anterior LV dysfunction. 130 In patients with established LVT who undergo PCI for an ACS or non-ACS indication we make the following recommendation.…”
Section: Lvt Formation After MImentioning
confidence: 99%
“…Both guidelines suggest reevaluation of LV thrombus with routine imaging and considering stopping anticoagulation with continuation of antiplatelet therapy. Prophylactic warfarin without LVT on echocardiography has been studied in high‐risk STEMI patients (anterior wall infarct and LVEF ≤ 40%) . It was not associated with reduced thromboembolic events but was associated with increased risk of bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…86 While some data suggest a benefit in preventing recurrent cardiovascular events, recent data have failed to find a decrease in the incidence of cardiovascular events, but did show a numerically increased rate of major bleeding. 87 Atrial thrombi most commonly involve the left atrial appendage and are most often associated with atrial arrhythmia. Treatment generally involves indefinite anticoagulation as is recommended for atrial fibrillation.…”
Section: Intra-cardiac Thrombimentioning
confidence: 99%
“…The role of prophylactic anticoagulation following anterior myocardial infarction is unclear . While some data suggest a benefit in preventing recurrent cardiovascular events, recent data have failed to find a decrease in the incidence of cardiovascular events, but did show a numerically increased rate of major bleeding …”
Section: Other Indications For Anticoagulation In Cardiac Patientsmentioning
confidence: 99%